MORPHOLOGICAL STUDIES ON THE STERNUM OF UMBRELLA COCKATOO (CACATUA ALBA) - A.R. Sreeranjini; N. Ashok; S. Pramod; S. Maya; J.J. Chungath (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted on the sternum of a five year old, male umbrella cockatoo brought for post mortem examination to the Department of Veterinary Pathology at the College of Veterinary and Animal Sciences, Mannuthy, Thrissur. The sternum was a light, quadrilateral bone with dorsal concave and ventral convex surfaces and four borders. The dorsal surface presented a few pneumatic foramina. The ventral surface furnished a large, boat shaped keel. The anterior and posterior borders were convex. The lateral border on either side presented five costal facets. The anterior extremity showed two distinct facets for coracoid. Craniolateral processes were short and hook shaped. Caudolateral processes fused with the median trabecula and hence the oval foramina were not present. The bifid rostrum was strong, tall and wide. The ratio of width of the sternum and its height was found to be 1.32mm. In overall appearance, the sternum of umbrella cockatoo showed the morphological features of flying group of birds.